2012
DOI: 10.5021/ad.2012.24.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma Concurrent with Bowen's Disease

Abstract: Merkel cell carcinoma (MCC) is a rare, aggressive cutaneous malignancy of the elderly and immunocompromised patients. It is occasionally found coexisting with other diseases, such as squamous cell carcinoma, basal cell carcinoma, actinic keratosis, miscellaneous adnexal tumors, and rarely Bowen disease. A 75-year-old woman presented with a 6-month history of an irregularly shaped erythematous patch on the left mandibular angle. Three months later, a 1.5×1.0 cm sized painless and rapidly growing erythematous no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…These findings suggest that in most of the cases the tumour cells were derived from Merkel cells of the hair follicle. The concomitant occurrence of MCC and other skin tumours (eg, SCC, Bowen's disease or BCC) has been reported in humans. In the present study, various degrees of irregular acanthosis and epidermal dysplasia were observed adjacent to the tumours in 9 cases (60%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that in most of the cases the tumour cells were derived from Merkel cells of the hair follicle. The concomitant occurrence of MCC and other skin tumours (eg, SCC, Bowen's disease or BCC) has been reported in humans. In the present study, various degrees of irregular acanthosis and epidermal dysplasia were observed adjacent to the tumours in 9 cases (60%).…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressed individuals are at higher risk of MCC . The concomitant occurrence of MCC and other skin tumours has also been reported …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…UV light is believed to be an important factor in the occurrence MCC concomitant with SCC . However, most cases of combined SCC and MCC affect primarily sun‐exposed areas of the skin, especially the face and neck in female patients . Our patient had MCC on her right breast, a sun‐spared area.…”
Section: Reportmentioning
confidence: 77%
“…1 However, most cases of combined SCC and MCC affect primarily sun-exposed areas of the skin, especially the face and neck in female patients. [7][8][9] Our patient had MCC on her right breast, a sun-spared area. Ho et al 3 reviewed 10 patients from arsenic endemic areas, and suggested the arsenic-related combined SCC and MCC tends to occur in non-sun-exposed areas, making this entity clinically distinct from UV-related combined SCC and MCC.…”
Section: Reportmentioning
confidence: 82%